Patients with AML and an IDH2-R172 mutation exhibit a unique initial response to intensive chemotherapy induction - Meira Yisraeli Salman; Alexander R. Terry; Andriy Derkach; David Nemirovsky; Kuo-Kai Chin; Yannis K. Valtis; Leora Boussi; Theresa Spivey; Wenbin Xiao; Christopher Famulare; Jenna Ciervo; Jacob M. Rowe; et al. (Blood Advances, 2025)
Abstract: The utility of a midcycle bone marrow biopsy (BMB) for early assessment of response in patients with acute myeloid leukemia (AML) after intensive chemotherapy (IC) induction is contested. Even when challenged, there is little consideration as to the possibility of different response dynamics among genetically defined subgroups. Clinical observations led to the hypothesis that patients with AML and mutations in IDH2-R172 (R172-m) exhibit particularly slow blast reduction after IC induction. The purpose of this study was to analyze response kinetics of patients with R172-m to IC and compare the dynamics to patients with AML and IDH2-R140 mutations (R140-m). A retrospective single-center analysis was conducted among patients with newly diagnosed IDH2-mutated AML who received IC induction. Dynamics of blast reduction were compared and correlated with outcomes. A total of 52 patients were identified; 33 with R140-m and 19 with R172-m. Patients with R172-m had significantly higher midcycle BMB median blast count (70% vs 5%; P < .001), and their BMBs were slightly more cellular (P = .045). Among the R140-m, 58% had ≤5% blasts vs 0 of the R172-m. Furthermore, it took significantly longer for patients with R172-m to achieve blast clearance (≤5% blasts in BMB) compared to those with R140-m (P = .017). However, there was no difference in overall survival between the 2 groups, and outcomes were similar and favorable. This type of slow blast reduction has only previously been described in patients with acute promyelocytic leukemia. These findings suggest judicial application of reinduction strategies in this subgroup and warrant further investigation.